Application of Loka Purusha Satmya Vada in Treating Filiform Wart - Anand D A,; Priya Padmanabhan, (International Journal of Ayurveda and Pharma Research, 2025)
Warts are cutaneous neoplasms caused by papilloma virus. Human papilloma viruses infects the epithelium of skin and mucous membranes. These infections may be asymptomatic, produces warts or may produce neoplasia. Filiform warts usually appear around the mouth, nose, under the chin or neck. They are long, narrow frond like benign growths. Even though these growths are asymptomatic they create a lot of cosmetic concern. In appearance these warts resemble sprouts coming from potatoes. Loka purusha Satmya vada told in Ayurveda classics tells us the relationship between universe and the humans. Thus the similarity in shape of filiform warts with potato sprouts tells the hidden remedy for these warts. Here the antimicrobial activity in potatoes was applied in treating the patient along with krimihara chikitsa.